Analysis of Jetty Structure Using the Fixity Point Method and Soil–Structure Interaction via the Spring Model - Rahmat Kurniawan; Ayu Sinta Aprilia; Mega Grace; Cahyo Agung Saputra; Ahmad Auliadi Yufrizal (Universitas Islam Raden Rahmat, Malang, 2025)
A jetty is an essential element of port infrastructure yet remains vulnerable to lateral forces generated by waves, currents, berthing impact, and earthquakes, all of which can trigger structural failure. This study analyzes jetty performance by comparing two design approaches, soil-structure interaction (SSI) modeled with non-linear springs, and the conventional fixity-point method. A reinforced-concrete deck on steel pipe piles was modeled in SAP2000, with pile diameters of 24, 32, and 40 inches embedded in medium sand. Serviceability and ultimate load combinations followed BS 6349 and ASCE 7-10 provisions. The SSI analysis showed larger structural responses than the fixity-point approach, with peak deflection, bending moment, axial force, and shear force increasing by approximately 35 %, 21 %, 12 %, and 18 %, respectively. These differences arise because the fixity-point method considers soil stiffness only to the calculated fixity depth, potentially underestimating overall lateral demand. Both approaches indicate that a 40-inch pile driven no deeper than 30 m satisfies deflection criteria while limiting drive length, offering a balanced solution between safety and economy. Verifying fixity-point designs with detailed SSI analysis is therefore recommended for robust jetty construction.